Precolonial Traditions and Practices of the Agta in San Mariano, Isabela - Luna, Gabriel (Social Sciences and Development Review, 2023)
The study aimed to record the precolonial traditions and practices on the life cycle of the Agta in Sitio Diwagdan, San Jose, San Mariano, Isabela relative to conception, child birth, child rearing, courtship, marriage, and death and burial; also to document how the Agta observe their precolonial traditions and practices along the following dimensions of life: social organization, religious practice, economic, politics, and education. Based from the discussions made and findings of the study, it can be concluded that the Agta have rich precolonial traditions and practices on life cycle relative to conception, childbirth, child rearing, courtship, marriage, and death and burial. They have limited social environment; they are animistic and open to other religious sects; they depend on hand to mouth subsistence as they rely much on rattan resources in the forest as the major source of their livelihood; the Agta political system is limited to their tribe in which they do not involve themselves in politics at the barangay level; and education for the Agta children is the least priority of the Agta parents